Utilization of PEGylated cerosomes for effective topical delivery of fenticonazole nitrate: in-vitro characterization, statistical optimization, and in-vivo assessment - Albash, Rofida (Drug Deliv, 2020)
In this investigation, we focused on ceramide IIIB, a skin component whose depletion tends to augment multiple skin disorders and fungal infections. Ceramide IIIB was included into PEGylated surfactant-based vesicular phospholipid system to formulate ‘PEGylated cerosomes’ (PCs) loaded with fenticonazole nitrate (FTN). FTN is a potent antifungal agent adopted in the treatment of mixed mycotic and bacterial infections. The ceramide content of the vesicles may provide protective and regenerative skin activity whereas Brij(®); the PEGylated surfactant, can enhance drug deposition and skin hydration. Both components are expected to augment the topical effect of FTN. PCs were prepared by thin-film hydration technique. A 2(3) full-factorial design was applied to study the effect of ceramide amount (X(1)), Brij type (X(2)) and Brij amount (X(3)) on the physicochemical properties of the formulated PCs namely; entrapment efficiency (EE%;Y(1)), particle size (PS;Y(2)), polydispersity index (PDI;Y(3)) and zeta potential (ZP;Y(4)). The optimal formula was selected for further in-vivo dermatokinetic and histopathological study. The optimal FTN-loaded PC (PC6) showed nanosized cerosomes (551.60 nm) with high EE% (83.00%w/w), and an acceptable ZP value of 20.90 mV. Transmission electron micrographs of the optimal formula illustrated intertwined tubulation form deviated from the conventional spherical vesicles. Finally, the dermatokinetic study of PC6 showed higher drug concentration and localization of FTN in skin layers when compared with FTN suspension and the histopathological study confirmed its safety for topical application. The overall findings of our study verified the effectiveness of utilizing PEGylated cerosomes to augment the activity of FTN as a topical antifungal agent.